Peran Etika Komunikasi Dalam Membentuk Budaya Organisasi Islami - Muhammad rifqi; Aditya putra helvani; Ismail Mubarok (PT. ALHAFI BERKAH INDONESIA, 2023)
The purpose of this article is to find out how important good communication etiquette is because we as human beings must have good etiquette when we speak so that people who communicate with us feel comfortable and will not be offended by what we say. This ethical culture must be instilled within us. ourselves in accordance with the teachings of Islam, especially those taught by the Al-Quran. Organizational culture is very important, especially in Islamic educational institutions, where it creates a culture that is flexible and never regressive, which when combined with a religion based on the Koran and Sunnah will make the institution perfect. In addition, religious individuals will separate their culture in the struggle for education itself if they cannot integrate religious teachings into their daily lives. marginalized in competition in the world of education itself, culture and ethics are very important in relation to our daily lives in small and large scopes, communication ethics is very important, namely it will make us more careful and clever in speaking. In Islamic organizations, manners and ethics of communication are highly prioritized, not only in our own country, but also in our own country. Even abroad, we are the same, so wherever we are, we should speak kind words.